Communist planning versus rationality mathematical economics and the central plan in eastern Europe and China - Kovács, János Mátyás (Revisiting communism: collectivist economic and political thought in historical perspective., 2022)
"This volume examines failed attempts at modernizing the communist economy by means of optimal planning. It traces the rise and fall of the concept in Eastern Europe and China, explaining why the mission of optimization was doomed to fail and why it may nevertheless be relaunched today"--